New airtight transfer box for SEM experiments: Application to lithium and sodium metals observation and analyses. (July 2018) - Stephant, Nicolas; Grissa, Rabeb; Guillou, Fanch; Bretaudeau, Mickaël; Borjon-Piron, Yann; Guillet, Jacques; Moreau, Philippe
Highlights: Scanning electron microscopy of pristine surface of lithium and sodium without aerobic exposure. New airtight transfer box for scanning electron microscopy from glove box to microscope chamber. Laboratory workshop made airtight transfer box conformable to all scanning electron microscopes. Abstract: The surface of some materials reacts very quickly on contact with air, either because it is oxidized or because it gets humidity from the air. For the sake of original surface observation by scanning electron microscopy (SEM), we conceived an airtight transfer box to keep the samples under vacuum from the place of manufacturing to the SEM chamber. This object is designed to fit in all the models of SEM including those provided with an airlock chamber. The design is voluntarily simplified to allow the manufacturing of the object by a standard mechanical workshop. The transfer box can be easily opened by gravity inside the SEM and allows the preservation of the best vacuum inside, before opening. SEM images and energy dispersive spectroscopy (EDX) analyses of metallic lithium and sodium samples are presented prior and after exposure to the air. X-ray Photoelectron Spectroscopy (XPS) analyses of all samples are also discussed in order to investigate the chemical environments of the detected elements.